Organoclay/functionalized-graphene dual-filler complex for high-performance polyimide nanocomposites - Hwang, Jun Yeon; Lim, Ae Ran; Chang, Jin-Hae (Royal Society of Chemistry, 2026)
Aromatic polyimides (PIs) are super engineering polymers with excellent mechanical properties and thermal stability, making them suitable for applications in semiconductor devices, displays, and electronic materials. In this study, a poly(amic acid) (PAA) was synthesized from dianhydride 4,4 '-biphthalic anhydride and diamine N,N '-[2,2 '-bis(trifluoromethyl)-4,4 '-biphenylene]bis(4-aminobenzamide) monomers, and a hybrid PAA was prepared by dispersing a complex filler using a solution intercalation method. The PAA hybrid solution was thermally imidized under various heat treatment conditions to obtain PI nanocomposite films. A novel complex filler containing both clay and graphene was synthesized through organic surface modification to improve compatibility and miscibility with the PI matrix. This dual-filler system was designed to enhance the overall performance of the PI hybrid films by exploiting the synergistic effects of both fillers. In this study, a C8-complex filler composed of octyl-modified montmorillonite and octyl-functionalized graphene was utilized. PI hybrid films were fabricated by dispersing the C8-complex filler into the PI matrix at various loadings ranging from 0 to 2.0 wt%. The effects of C8-complex filler content on the dispersion morphology, thermomechanical properties, and optical transparency of the resulting PI hybrid films were systematically investigated.